Development and Validation of Lecture Maker-Based Biology Learning Media on Excretory System Material - Muhammad Syahrul; Riska Herlena Sitompul; Ine - Arini (Journal of Biological Science and Education, 2025)
Biology learning, particularly the abstract topic of the Excretory System, demands high visualization, which is often lacking in conventional media. This Research and Development (RD) study, utilizing the ADDIE model and focusing on the validation stage, aimed to develop and assess the academic feasibility of a digital learning medium based on Lecture Maker software. Following a thorough analysis of curriculum objectives and student needs, the product was designed to integrate text, images, animations, and videos to present complex physiological concepts. Product validity was rigorously assessed by both subject matter and media experts, yielding an average total score of 4.15, which categorizes the medium as "Valid". Detailed results showed high scores for design/structure (4.19) and language (4.50), while the content/substance aspect received the lowest rating (Sufficiently Valid, 3.76), indicating specific areas for revision concerning the simplification of scientific language and enhanced visualization. In conclusion, the developed Lecture Maker-based medium is declared academically feasible and valid, fulfilling the criteria for quality educational media and is ready to be utilized in the subsequent implementation stage to assess its practical effectiveness on student learning outcomesKeywords:  Lecture Maker,  Learning Media,  Excretory System,  Validation,  ADDIE Model